HUBUNGAN BERMAIN GAME ONLINE DENGAN PRESTASI BELAJAR MATEMATIKA ANAK USIA SEKOLAH KELAS V DI SEKOLAH DASAR - Ni Putu Marlina (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Games is a part of the growth process on school-age children. Games with competition characteristic become one of the favourite games for children that is game online. However, uncontrolled play can influence children’s concentrate on mathematics study. This study aimed to determine the correlation between play game online with achieved mathematics study on 5th grade school in Elementary School Saraswati 1 Denpasar. This study was correlation study with cross sectional approach. Samples consist of 50 childrens were selected with non probability sampling with purposive sampling technique. The analysis by the rank spearman resulted p value 0,000 with correlation coefficient value -0,732 that mean, of there was strong correlation with negative relationship, it can conclude more often the children playing games online than the children will get worse achieved on mathematics study. It can be suggested to the health physicion and schooling to give dissimination the negative impact of game online